Determination of organic content and the use of eco-enzyme solutions in reducing organic levels in water samples from Cukuh Raya Beach, Kaur Regency, Bengkulu Province, Indonesia - Noviana, Noni; Johan, Henny; Mayub, Afrizal; Nurhamidah; Firdaus, M. Lutfhi (JASM, 2024)
Cukuh Raya Beach coastal water is potentially polluted by organic materials from shrimp ponds. The purpose of this study was to determine the content of organic materials (ammonia [NH3], nitrate [NO3], phosphate [PO4], and fatty oil) discharged into the coastal waters and to examine the role of eco-enzymes in reducing the organic material levels. Two points of sampling were selected, i.e., 10 and 100 m from the pipeline outfall discharge of shrimp ponds. An experiment was carried out to compare the level of organic content before and after the eco-enzyme solutions were given. Sampling and technique analysis of seawater were done following the Indonesian National Standards. The data were analysed using the Indonesian quality standards for marine biota and the pollution index. The results showed that seawater samples from the coast contained organic waste, with the highest levels at 10 m from the outfall. The level of organic content decreased after the addition of eco-enzyme solutions. The conclusion is that the organic materials (ammonia, nitrate, phosphate, and fatty oil) were found in water samples in the waters of Cukuh Raya Beach and were moderately polluted by ammonia (NH3). The addition of an eco-enzyme solution can reduce the concentration of organic materials.